Atomistic simulation for deforming complex alloys with application toward TWIP steel and associated physical insights. (January 2017) - Wang, Peng; Xu, Shaofeng; Liu, Jiabin; Li, Xiaoyan; Wei, Yujie; Wang, Hongtao; Gao, Huajian; Yang, Wei
Abstract: The interest in promoting deformation twinning for plasticity is mounting for advanced materials. In contrast to disordered grain boundaries, highly organized twin boundaries are beneficial to promoting strength-ductility combination. Twinning deformation typically involves the kinetics of stacking faults, its interplay with dislocations, as well as the interactions between dislocations and twin boundaries. While the latter has been intensively studied, the dynamics of stacking faults has been rarely touched upon. In this work, we report new physical insights on the stacking fault dynamics in twin induced plasticity (TWIP) steels. The atomistic simulation is made possible by a newly introduced approach: meta-atom molecular dynamics simulation. The simulation suggests that the stacking fault interactions are dominated by dislocation reactions that take place spontaneously, different from the existing mechanisms. Whether to generate a single stacking fault, or a twinning partial and a trailing partial dislocation, depends upon a unique parameter, namely the stacking fault energy. The latter in turn determines the deformation twinning characteristics. The complex twin-slip and twin-dislocation interactions demonstrate the dual role of deformation twins as both the dislocation barrier and dislocation storage. This duality contributes to the high strength and high ductility of TWIP steels.